Downgraded by Upgrading: Small-scale Traders, Urban Transformation and Spatial Reconfiguration in Post-reform Vietnam - Endres, Kirsten W. (Cambridge anthropology, 2014)
This article examines some of the ruptures and contestations that have emerged in the context of urban restructuring and market redevelopment policies in Hanoi, Vietnam. Public markets have become sites of contestation and struggle over the commoditization and use of public urban space: large plots of state-owned real estate in the inner city are handed over to private investment companies for development, in the process of which small-scale traders are losing their means of economic survival in the marketplace. These forms of accumulation by dispossession likewise reflect processes of social and spatial reconfiguration that exclude the urban poor and other 'uncivilized' subjects from public visibility by creating up-scaled spaces of lifestyle and consumption for the newly emerging classes of high-end consumers. Such processes of dispossession are gendered and impact on different kinds of traders in different ways.